Calreticulin in Essential Thrombocythemia: StressINg OUT the Megakaryocyte Nucleus - Iborra, Francisco Jose; Papadopoulos, Petros (Frontiers in Oncology, 2017)
Calreticulin (CALR) is a multifaceted protein primarily involved in intracellular protein control processes. The identification of CALR mutations in essential thrombocythemia (ET) and primary myelofibrosis that are mutually exclusive with the JAK2 V617F mutation has stirred an intensive research interest about the molecular functions of CALR and its mutants in myeloproliferative neoplasms (MPNs) and its diagnostic/prognostic value. The recently characterized protein–protein interaction of CALR mutants and MPL receptor has advanced our knowledge on the functional role of CALR mutants in thrombocythemia but it has also uncovered limitations of the current established research models. Human cell lines and mouse models provide useful information but they lack the advantages provided by ex vivo primary cultures of physiologically relevant to the disease cell types [i.e., megakaryocytes (MKs), platelets]. The results from gene expression and chromatin occupancy analysis have focused on the JAK-STAT pathway activated in both JAK2 V617F- and CALR-mutated MPN patient groups, although a more complete analysis is needed to be performed in MKs. Stress related processes seem to be affected in CALR mutant ET-MKs, but the precise mechanism is not known yet. Herein, we describe a culture method for human MKs from peripheral blood progenitors, which could help further toward an unbiased characterization of the role of CALR in ET and MK differentiation.